Factors in the Formation of Patriotic Values and Attitudes in High School Seniors (Case Study of Siberian Federal District) - Sergey Yu. Assev; Yaroslava Yu. Shashkova (National Research Mordova State University, 2022)
Introduction. The issue of patriotism tends to be one of the most discussed in official discourse on the Russian youth. Still the issue lacks explicit conceptual interpretation and consistent mechanism of implementation at different levels. The article aims at evaluating the scope of influence of the specifics of the regions, their socio-cultural, informational and institutional environment on the way senior school children understand patriotism, the type of patriotism dominating their conscience and their attitude to patriotic education in Russia. Materials and Methods. The article draws on the surveys of the pupils of 8th-11th grades of secondary schools in 10 regions of Siberian Federal District (n =2 050 people; non-linked quota samples with monitoring age, grade, type of locality and region). The data were collected through direct questionnaires at the respondentsʼ place of study. Results. The article has revealed prevailing emotional interpretation of patriotism by senior school children. The model of "blind" patriotism and its activity-orientated interpretation are wide-spread among school children of national republics, while "constructive" patriotism is spread among school children of administrative regions. The factors determining this split are peculiarities of the environment, values, current and prospective political involvement of the youth, the level of its trust for social and political institutions. The article has traced the influence of the dominant models of patriotism and the degree of school children involvement into the system of patriotic education on their attitude to this system, their evaluation of its forms and methods. Based on the conducted survey the article has proved the consistency of applying models of "constructive" and "blind" patriotism to composite societies on both a country and a region level. Discussion and Conclusion. The conclusions and the materials of the research can be useful for state departments of youth policy, youth social and political organizations, institutions of education as well as for research in politics and sociology of youth.